About time: Rainer Maria Rilke and the abyssal distance of Duino Elegies. Issue 10 (3rd October 2022) - Mukim, Mantra
ABSTRACT: The speaker of Duino Elegies treats time as a threat to its sense of situatedness and privacy; a threat that taints all its modes of inhabiting and surviving in the world. This essay argues that Rilke's foremost task in Elegies is to expose every aspect of subjectivity to such a threat. Arguing against the phenomenological readings of Rilke, that continue to misread the 'open'-ness in his work as a non-dualist or an antediluvian gesture, this essay contends that the Rilkean 'open' is not a counterpoint to our everyday habitus nor does it untether the subject from its finite conditions of time and space, rather it creates a radical, and literary, necessity for finitude. The elegy form, with its traditional emphasis on loss and rehabilitation through memory and poetic authority, is refashioned by Rilke to a degree where what is lost is never allowed a birth into presence either in consciousness or in language. Drawing upon Derrida's critique of Husserl, the essay argues that Rilke's work is at its most singular precisely when it searches for a place within time and not despite it.